Urgency of State Administration Innovation System (SINAGARA) on Regional Government Performance - Dewi Sartika (Policy & Governance Review, 2019)
The era of information disclosure is characterized by increasingly sophisticated information technology and well-educated society. That matter has implications for the demands of increasing the quality of public services managed by the government, amid the limitations of the budget, human resources, institutions, and governance. This research encourages the development of the state administration innovation system (SINAGARA) to leverage the performance of regional government. The ways can be taken is to establish an innovation implementation unit/task force where the Regional Research & Development Agency as the leading sector, provide incentives for tasks unit Innovators and innovator agents and encourage innovation-based budgeting. The importance of building a state administration innovation system (SINAGARA) for regional governments-by utilizing developing information technology - is an indicator of regional head and high leadership performance, and optimizing the role of regional government as the leading sector of development the state administration innovation system.